EFEKTIFITAS PENGELOLAAN APBDes MENGGUNAKAN SISTEM KEUANGAN DESA (SISKEUDES) : (Studi di Desa Wandanpuro – Kecamatan Bululawang – Kabupaten Malang) - Rohman Kusmayadi, Rudy Catur (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2023)
The purpose of this study is to find out and analyze how effective the use of the village financial systems to minimize and anticipate misuse of village funds and to support transparent, accountable and participative in village financial management regulations. The government is working with the Ministry of Home Affairs and BPKP to develop an application called the Village Financial System (Siskeudes). This research focuses intensively on one particular object, called case study. Data collection was carried out by interview, observation, and documentation methods. The research subjects were the Village Head, Village Secretary, Head of Finance, and village financial system application operators. The research object is the application of the village financial system. The results of this study are that the application of the village financial system is able to improve village financial governance starting from the planning, implementation and reporting/evaluation stages so that it can be structured into a more orderly and detailed manner. Meanwhile, the strategy undertaken in dealing with the obstacles faced by the Village government is to increase understanding and skills in operating the Village Financial Governance System Application by participating in training and practicing the Operating Instructions for the Village Financial Governance System Application. Key words: effectivity; finance; government; management; system